2010
DOI: 10.1177/0003319710362975
|View full text |Cite
|
Sign up to set email alerts
|

Resting Muscle Oxygen Consumption by Near-Infrared Spectroscopy in Peripheral Arterial Disease: A Parameter to be Considered in a Clinical Setting?

Abstract: Resting muscle VO( 2) consumption (rmVO(2)) as measured by near-infrared spectroscopy (NIRS) has been poorly studied in peripheral arterial disease (PAD). We studied the feasibility of its assessment in a clinical setting, compared values from PAD and healthy participants, and identified factors affecting rmVO( 2) in PAD. A total of 119 PAD patients with claudication and 30 healthy participants were enrolled. Ankle brachial index (ABI), adipose tissue thickness, and rmVO(2) in the gastrocnemius after venous (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 32 publications
(60 reference statements)
6
57
1
1
Order By: Relevance
“…It was recommended that biomarkers of muscle function related to clinical status be tested and applied to develop biological models of recovery in severe, disabling diseases like stroke [31] . Findings in this study in ESRD patients and observations on other chronic conditions [5,6] concur in supporting rmVO 2 as a biomarker of peripheral deconditioning in ESRD patients. In this study, we document that rmVO 2 is not a mere surrogate of other risk factors or disease markers.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…It was recommended that biomarkers of muscle function related to clinical status be tested and applied to develop biological models of recovery in severe, disabling diseases like stroke [31] . Findings in this study in ESRD patients and observations on other chronic conditions [5,6] concur in supporting rmVO 2 as a biomarker of peripheral deconditioning in ESRD patients. In this study, we document that rmVO 2 is not a mere surrogate of other risk factors or disease markers.…”
Section: Discussionsupporting
confidence: 87%
“…Along with our working hypothesis, we found that rmVO 2 in resting condition was much higher in ESRD patients than in coeval healthy subjects. Of note, rmVO 2 in these patients (0.083 ± 0.034 ml/100 g/min) was also higher than that we had previously observedunder the same experimental conditions and with the same NIRS device -in patients with peripheral artery disease (0.069 ml/100 g/min) [5] and in those with multiple sclerosis (0.059 ml/100 g/min) [6] . The increased muscle oxygen consumption in ESRD patients was un- Paired sample t-test (* p < 0.05).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations